Pengaruh keselamatan dan kesehatan kerja (k3) terhadap kinerja karyawan divisi usaha sarana produksi peternakan Koperasi Serba Usaha Tandangsari - Indra, Nurhayat; Sumaryana, Fitriana Dewi; Abdulloh, Muhtar Sahid (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The Business Division of Animal Husbandry Production Facilities at KSU Tandangsari experiences fluctuations in income, the percentage of income attainment, employee productivity, and the percentage of achieving ideal productivity per employee, which tends to decrease every year, which indicates problems in business management based on problematic employee performance. This study aims to examine the effect of occupational safety and health on employee performance, both partially and simultaneously, so that any efforts can be formulated that can improve employee performance in the future through existing variables. The method used is a quantitative research method using a descriptive and verification approach. The population of this study were employees of the Livestock Production Facility Business Division at KSU Tandangsari. This study used a saturated sampling technique with 13 respondents. The analytical method used is multiple linear regression analysis and hypothesis testing. Based on the results of the study, it can be concluded that work safety, occupational health, and employee performance in the Animal Husbandry Production Facilities Business Division are in the sufficient category. Then occupational safety and health have no significant effect on employee performance, either partially or simultaneously. So that effective efforts cannot be made to improve employee performance through occupational safety and health.